Identifying and Explaining Green Supply Chain Management Practices with a Focus on Technical Perspectives for Performance Improvement - Nourizadeh Firouzabadi , Ali; Dehghan Dehnavi, Hassan; Taghi Honary , Mohammad; Rabbani, Mozhde; Sadeghian, Abolfazl (Management Strategies and Engineering Sciences, 2025)
The objective of this study is to design a model for green supply chain management practices with an emphasis on technical factors for localized performance improvement in the tile and ceramic industry. The research methodology is based on the interpretive paradigm, developmental in purpose, and employs an inductive approach with an exploratory-analytical nature. It is conducted as a mixed-method study, drawing on a target population of industry and academic experts and using purposeful sampling. The research consists of three steps. The first step identifies green supply chain management practices emphasizing technical factors for performance improvement through content analysis of national and international publications. The second step localizes the extracted practices, focusing on the tile and ceramic industry, using the Delphi method. The third step involves ranking the factors and presenting a model. The study introduces green supply chain management practices with a focus on technical factors for performance improvement and explores the relationships between these practices to provide managers with actionable insights. The proposed model encourages managers to prioritize factors such as research and development, continuous analytical review of machinery operational status, and comprehensive analytical evaluation of all stages of production processes, which are identified as the most influential practices.